Machine, platform, crowd : harnessing our digital future - McAfee, Andrew; Brynjolfsson, Erik (New York W. W. Norton and Company, 2017)
"We live in strange times. A machine plays the strategy game Go better than any human; upstarts like Apple and Google destroy industry stalwarts such as Nokia; ideas from the crowd are repeatedly more innovative than corporate research labs. MIT’s Andrew McAfee and Erik Brynjolfsson know what it takes to master this digital-powered shift: we must rethink the integration of minds and machines, of products and platforms, and of the core and the crowd. In all three cases, the balance now favors the second element of the pair, with massive implications for how we run our companies and live our lives. In the tradition of agenda-setting classics like Clay Christensen’s The Innovator’s Dilemma, McAfee and Brynjolfsson deliver both a penetrating analysis of a new world and a toolkit for thriving in it. For startups and established businesses, or for anyone interested in what the future holds, Machine, Platform, Crowd is essential reading." (from Amazons page)
Chapter 1: The triple revolution -- Part 1 Mind and machine -- Chapter 2: The hardest thing to accept about ourselves -- Chapter 3: Our most mind-link machines -- Chapter 4: Hi, Robot -- Chapter 5: Where technology and industry still need humanity -- Part 2 product and platform -- Chapter 6: The toll of a new machine -- Chapter 7: Paying complements, and other smart strategies -- Chapter 8: The match game:why platforms excel -- Chapter 9: Do products have a prayer? -- Part 3 Cord and crowd -- Chapter 10: That escalated quickly the emergence of the crowd -- Chapter 11: Why the expert you now is not the expert you need -- Chapter 12: The dream of decentralizing all the things -- Chapter 13: Are companies passe? -- Conclusion: Economies and societies beyond computation
Includes bibliographical references and index.
Keywords: Information technology; INFORMATION TECHNOLOGY; ECONOMIC ASPECTS; Social aspects; ECONOMIC DEVELOPMENT; TECHNOLOGICAL INNOVATIONS